The Psychological Benefits of an Uncertain World: Hope and Optimism in the Face of Existential Threat - Smithson, Michael; Shou, Yiyun; Dawel, Amy; Calear, Alison L.; Farrer, Louise; Cherbuin, Nicolas (Frontiers in Psychology, 2022)
We examine how prior mental health predicts hope states and how hopes predict subsequent mental health, testing hypotheses in a longitudinal study with a representative Australian adult sample regarding mental health consequences of the COVID-19 outbreak. Greater anxiety, depression, distress, and loneliness predict less hope, but impaired quality of life and stress positively predict hopes of gaining new skills. Distress and loneliness predict hopes for social connectedness and an improved society, suggesting that predictors of hope depend on what is hoped for. Greater hopes for societal improvement predict lower anxiety, depression, distress, and impaired quality of life, but greater hopes for skills and better mental health predict higher levels of these covariates. Moreover, when relevant prior psychological states are more intense, the impact of hope state declines. These findings suggest the consequences of hope are heterogeneous, and a possible explanation for the seemingly inconsistent therapeutic effectiveness of raising hope.